Review of the potential for recycling CO2 from organic waste composting into plant production under controlled environment agriculture. (20th January 2022) - Thomson, A.; Price, G.W.; Arnold, P.; Dixon, M.; Graham, T.
Abstract: Composting has been used extensively as a sustainable approach for the management organic waste streams and conversion into stabilized soil amendments and horticultural growth media. In addition to these products, the composting process also generates by-products of microbial metabolism that includes gas (CO2 ) and energy (heat). High rates of food waste and commercial organic waste generation, along with greater diversion away from landfills, creates new opportunities to valorize these by-products from aerobic composting. Specifically, integrating carbon dioxide recapture and recycling into Controlled Environment Agriculture (CEA) production systems presents a pathway to circularize resources. CEA systems produce plants year round in an environmentally controlled space where elevating CO2 environments can boost plant production, creating a synergistic relationship with composting processes. The review evaluated CO2 emissions from an array of open and closed composting systems, as well as different feedstocks to demonstrate its potential for use in CEA. Rates of CO2 emissions varied widely, with a peak CO2 emission range of 0.32–429.27 g CO2 –C kg −1 d −1 depending on the aeration conditions and feedstock composition. Analysis of two hypothetical CEA scenarios reveals that integrating in-vessel composting as an on-site waste management process is comparable in cost to using natural gas as a regular CO2 source. The quantity of composting feedstocks required to generate CO2 emissions for a single tier and five tier CEA lettuce production system ranged from 3.38 to 69.94 kg dry biomass d −1 and 9.93–205.50 kg dry biomass d −1, respectively, but varied based on feedstock composition and compost operating conditions. The long-term research goal is toward valorizing non-edible biomass of CEA systems to create a circular economy model of commercial plant production. Graphical abstract: Image 1 Highlights: Composting organic wastes generate significant quantities of metabolic CO2 . CO2 gas from municipal and agricultural organic are used for plant production. Peak CO2 gas production occurs more rapidly in enclosed composting systems. Growth in Controlled Environment Agriculture valorizes CO2 recycling from organic wastes. Integrating in-vessel composting with closed environmental agriculture creates new economic synergies.